Socio-Economic contribution of Schinziophyton rautanenii to rural livelihoods of Hwange District, Zimbabwe - Mpofu, Ashley; Chichinye, Angella; Kundishora, Kudzai N; Mlambo, Donald; Dube, Caleb (Journal of Forests, 2025)
This study investigated the socio-economic contribution of Schinziophyton rautanenii in Hwange District, Zimbabwe. Purposive sampling was conducted, and Schinziophyton rautanenii harvesters were interviewed. The assessment focused on knowledge about the species’ role in the environment, willingness to conserve Manketti, and the impact of distance on the amount of nuts harvested per season. Additionally, the economic contribution was evaluated using Plant Part Value (PPV) and Use Value Index (UVk). Data analysis was done in PAST and R Studio statistical package. Chi-squared test was used to test for associations, T-test was used to analyze uses among different categories and ANOVA among different age groups. Chi-squared test results showed that the knowledge on species’ role in the environment was dependent on age and gender. Willingness to conserve was dependent (p<0.001) on the knowledge of species’ role in the environment, whereas proximity to protected areas influenced the amount of nuts harvested (p<0.001). Among the plant parts used, fruits were the most used, with 36%, and among the Use Value Index, food was the most valued. Scientifically, all the categories valued the species equally. In conclusion, there is a need to address these knowledge gaps, educate, and promote the social and cultural use of the species.